Intellectual development in Apert's syndrome: a long term follow up of 29 patients. Issue 3 (March 1988) - Patton, M A; Goodship, J; Hayward, R; Lansdown, R
Abstract : Twenty-nine patients with Apert's syndrome were ascertained through hospital records. The mean age was 19.3 years (range eight to 35 years). Further information was obtained on their intelligence, education, and employment records. Fourteen patients (48%) had a normal or borderline IQ (greater than 70), nine patients (31%) were mildly mentally retarded (IQ 50 to 70), four patients (14%) were moderately retarded (IQ 35 to 49), and two patients (7%) were severely retarded (IQ less than 35). Early craniectomy did not appear to improve intellectual outcome. Six of the seven school leavers with normal or borderline intelligence were in full time employment or vocational training.